(untitled) - Barry F Wellington (London, 1995)
The book covers the fundamentals of traditional engines and fuel systems. For the first time, the book illustrates and explains the complete working of diesel engine and its fuel injection systems. It explains in detail the construction and servicing of the cylinder head and valves, cylinder block, crankshaft assembly, pistons, rings and connecting rods, timing gears, camshaft and rocker gear assembly. It features the chapters on bearings and seals/gaskets; includes information on electronic fuel injection control and engine management; explains the Celect electronic fuel injection system; contains information on the electroniccally controlled 3176 engines; explains the ways in which faults within the system can be identified and repaired; illustrates and explains the opperation of the various sensors used in the electronic engine management system; features turbocompounding, how its works and why it is used on diesel engines. Finally, as emission controls are becoming stricter with diesel engines, some of the side-effects are starting to become apparent
Keywords: diesel motor - fuel system